2012
DOI: 10.1182/blood-2011-11-389585
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-9 binding to Tim-3 renders activated human CD4+ T cells less susceptible to HIV-1 infection

Abstract: Galectin-9 (Gal-9) is a tandem repeat-type member of the galectin family and is a ligand for T-cell immunoglobulin mucin domain 3 (Tim-3), a type-I glycoprotein that is persistently expressed on dysfunctional T cells during chronic infection. Studies in autoimmune diseases and chronic viral infections show that Tim-3 is a regulatory molecule that inhibits Th1 type immune responses. Here we show that soluble Gal-9 interacts with Tim-3 expressed on the surface of activated CD4 ؉ T cells and renders them less sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
129
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 113 publications
(143 citation statements)
references
References 51 publications
13
129
0
Order By: Relevance
“…Gal-9 is highly expressed in tissues of the immune system, including bone marrow, lymph nodes, liver, thymus, and spleen, and patients with chronic viral infection have elevated circulating levels (3,4). Gal-9 has complex immunomodulatory roles involving effector cells of both innate and adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gal-9 is highly expressed in tissues of the immune system, including bone marrow, lymph nodes, liver, thymus, and spleen, and patients with chronic viral infection have elevated circulating levels (3,4). Gal-9 has complex immunomodulatory roles involving effector cells of both innate and adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Gal-9 is widely distributed throughout various tissues, being particularly abundant in the liver (2). We have demonstrated that Gal-9 circulates at very high levels in the serum, and its hepatic expression is significantly increased in patients with chronic hepatitis C virus (HCV) compared to normal controls (3), and others have found high levels of Gal-9 in patients with HIV (4). Gal-9 interacts with various ligands, the best characterized of which is the T cell immunoglobulin mucin 3 (Tim-3) cell surface molecule, widely expressed on innate and adaptive immune cells (5).…”
mentioning
confidence: 93%
“…Indeed, individuals infected with hepatitis C virus (HCV), HIV-1, dengue virus, and influenza virus have higher serum levels of Gal-9 (6,(22)(23)(24), yet the mechanism responsible for such increases has not been identified. Given the critical role of type I IFNs in controlling viral infections, it is tempting to speculate that IFN-␤ may be an essential driver of Gal-9 upregulation.…”
Section: Upregulation Of Galectin 9 By Hcmv Is Via Induction Of Intermentioning
confidence: 99%
“…Gal-9 can play an important role in virus life cycles. It modulates human immunodeficiency virus type 1 (HIV-1) entry (6,7), while Gal-9-knockout mice exhibit more potent antiviral T-cell responses than wild-type mice (8,9), and infection with Epstein-Barr virus (EBV) modulates Gal-9 expression to evade immune clearance, inducing apoptosis of EBV-specific CD4 ϩ T cells (10,11). We investigated the expression of Gal-9 in the context of HCMV infection both in vivo and in vitro, identifying a novel, virally induced mechanism to promote Gal-9 expression.…”
mentioning
confidence: 99%
“…Furthermore, we showed that Gal-9 binding to Tim-3 renders activated human CD4 + T cells less susceptible to HIV-1 infection (46). Since Gal-9 can inhibit infection by influenza virus, it is suggested that Gal-9 is also a useful therapy for HIV infection.…”
Section: F Gal-9 In Infectious Diseasesmentioning
confidence: 88%